2009
DOI: 10.1108/13663666200900045
|View full text |Cite
|
Sign up to set email alerts
|

Developing services for people with dementia

Abstract: Health and social care agencies located in rural areas face particular challenges if they are to be able to effectively support people with dementia within their communities. Ann McDonald and Becky Heath describe a piece of work carried out in three rural counties in East Anglia that mapped services across the statutory, voluntary and private sectors and explored how national policy was being interpreted to meet local need. The findings confirm that services for older people with dementia are under-developed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Similarly, Alzheimer Society staff reported fewer services provided by other organizations (e.g., day programs) in rural compared to urban locations (Herron et al, 2016). Particular gaps in services were reported for people with young onset dementia and those belonging to an ethnic or sexual minority group (McDonald & Heath, 2009;Moore, 2002). Finally, limited choices in type, amount, and provider were identified even when services were available (Forbes et al, 2011;Forbes et al, 2013;Innes, Sherlock, & Cox, 2003;Kelsey & Laditka, 2006;Mason et al, 2005;O'Reilly & Strong, 1997).…”
Section: Education and Support Service Needs Availability And Usementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Alzheimer Society staff reported fewer services provided by other organizations (e.g., day programs) in rural compared to urban locations (Herron et al, 2016). Particular gaps in services were reported for people with young onset dementia and those belonging to an ethnic or sexual minority group (McDonald & Heath, 2009;Moore, 2002). Finally, limited choices in type, amount, and provider were identified even when services were available (Forbes et al, 2011;Forbes et al, 2013;Innes, Sherlock, & Cox, 2003;Kelsey & Laditka, 2006;Mason et al, 2005;O'Reilly & Strong, 1997).…”
Section: Education and Support Service Needs Availability And Usementioning
confidence: 99%
“…Collaboration between organizations and sectors was suggested as a feature of high-quality service provision and a way to enhance service accessibility (Clancy, 2015;Forbes et al, 2012;Innes et al, 2006;Mason et al, 2005;McDonald & Heath, 2009;O'Reilly & Strong, 1997). Service providers in Innes et al's (2006) research reported that effective partnerships with other agencies allowed them to share knowledge, funding, and transportation schemes, strengthening the accessibility and quality of services (see also Mason et al, 2005).…”
Section: Inter-organization Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…A search of the literature revealed that the investigation into the dementia experience in rural northern communities has been largely untouched, with the exception of a few pockets of research occurring in Canada and elsewhere (Edelman, Kuhn, Fulton, & Kyrouac, 2006; Morgan et al, 2002). McDonald and Heath (2008) examined the provision of health and social services for people with dementia in three rural communities in the United Kingdom and found an underdevelopment of dementia care services and policies. Interestingly, the authors pointed out that carers were also quite aware of the “rationing” of services and, although discouraged by the limited availability of professional supports, had an expectation and sense of entitlement to support from within the community that was fulfilled by family, volunteers, and other community members (McDonald & Heath).…”
mentioning
confidence: 99%
“…In Canada, rural family caregivers reported fewer service options for community-based dementia services than those in urban settings (Forbes et al, 2008) . A study of service provision in rural England (McDonald & Heath, 2009) identified gaps including patchy service provision, absence of training opportunities, and difficulties recruiting staff.…”
Section: Primary Health Care Orientation Of Dementia-related Servicesmentioning
confidence: 99%